Pelatihan Literasi Numerasi untuk Guru SDI Khazanah Kebajikan: Kunci Pembelajaran Matematika yang Menyenangkan: Numeracy Literacy Training for Teacher of SDI Khazanah Kebajikan: the Key to Enjoyable Mathematics Learning - Septiarini, Tri Wijayanti; Pariyanti, Eka; Muna, Siti Umamah Naili; Hidayat, Wahyu; Mahira, Putri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
To support improvements in basic education quality, particularly in numeracy literacy, a community service program was conducted at SDI Khazanah Kebajikan, Pondok Cabe Ilir, Pamulang, South Tangerang. The program aimed to strengthen teachers' competencies in designing and delivering numeracy learning that is contextual, interactive, and life-relevant. Employing a Community Development approach, the program involved a needs assessment, teacher training, mentoring (both in-person and online), distribution of teaching aids and contextual numeracy books, and a thorough evaluation. Training focused on problem-based learning strategies, the use of simple instructional media, and the integration of religious and local cultural values into mathematics teaching. Mentorship helped teachers tackle classroom challenges and apply new methods effectively. The results indicated a positive impact: increased teacher knowledge, confidence, and motivation in teaching numeracy. Teachers also demonstrated improved ability to design innovative, student-centered instruction. Additionally, there were early signs of increased student engagement following the application of the training outcomes. This activity not only enhanced teacher capacity but also contributed to elevating the overall quality of primary education through culturally responsive and meaningful numeracy learning.